2008
DOI: 10.1590/s1516-80342008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Adesão ao tratamento fonoaudiológico segundo a visão de ortodontistas e odontopediatras

Abstract: OBJETIVO: Verificar a percepção de ortodontistas e odontopediatras de Belo Horizonte e Itabira sobre a adesão à fonoterapia. MÉTODOS: Estudo transversal realizado, por meio de aplicação de questionário, com 30 ortodontistas e 30 odontopediatras, metade de cada cidade. Na análise estatística empregou-se o Teste Qui-quadrado. RESULTADOS: Todos dos profissionais consideram importante a atuação fonoaudiológica e encaminham com freqüência seus pacientes para tratamento, sendo que 58,3% relataram que os pacientes ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
8
0
4
Order By: Relevance
“…In the literature, there are few specific reports of bite changes and facial asymmetry in patients with IP. However, these features could be the result of frequent dental anomalies, which potentially would bring consequences for the form and function of the stomatognathic system (22)(23)(24) . Regarding the increased frequency of high hard palate in our sample (71.4%), in a systematic review conducted in the period between 1993-2012, with 1,286 patients diagnosed with IP, where only 513 provided sufficient information to evaluate possible dental and oral anomalies, aged from 1 year, it was observed that 54.4% had some dental and/or oral anomaly, and high hard palate was one of the most frequent oral abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are few specific reports of bite changes and facial asymmetry in patients with IP. However, these features could be the result of frequent dental anomalies, which potentially would bring consequences for the form and function of the stomatognathic system (22)(23)(24) . Regarding the increased frequency of high hard palate in our sample (71.4%), in a systematic review conducted in the period between 1993-2012, with 1,286 patients diagnosed with IP, where only 513 provided sufficient information to evaluate possible dental and oral anomalies, aged from 1 year, it was observed that 54.4% had some dental and/or oral anomaly, and high hard palate was one of the most frequent oral abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics can be explained by the close relationship between bone/dental and muscular conditions and functions of the stomatognathic system. The face is an interdependent system and any change in one of its components will result in a general disharmony (23) . In mouth breathers, for example, the tongue tends to remain lower in the oral cavity, which can cause changes in muscle and stomatognathic system functions, including speech production (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The Speech Therapy is a profession in expansion and development in Brazil, especially when viewed through the prism of recognition and official government definition and its inclusion in Public Health Programs 1,2 . All government moves to improve care and access to health care has located the professional speech therapist as an important engine for the development of the public health service.…”
Section: Introductionmentioning
confidence: 99%
“…Their essential characteristics, although encouraged by a clinical rigor, took their professional walking toward interdisciplinarity. There are, clearly, the magnitude of the significant exchange of knowledge and experiences with other areas of professionals, mainly of Dentistry and Medicine [1][2][3] . The world's scientific literature is replete with present relevant researches on caries in children 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation